Incitement: Anwar al-Awlaki's western jihad - Meleagrou-Hitchens, Alexander (Harvard University Press, 2020)
Part one. The making of a global jihadist leader: From America to Yemen -- Awlaki and activist Salafism -- Awlaki and Salafi-jihadism: theory and praxis -- "And inspire the believers..." -- Part two. Awlaki's disciples: Umar Farouk Abdulmutallab -- Nidal Hasan -- Zachary Adam Chesser -- Awlaki and the Islamic State in the West.